Forecasting catastrophic events in technology, nature and medicine - Panda, Anton; Nahornyi, Volodymyr (Springer, 2021)
This book presents a methodology for forecasting events and phenomena occurring in technology and natural environments. The methodology is based on forecasting the individual state of the control object, which is carried out based on the analysis of the trend behavior of the controlled parameter (symptom of the disease). The methodology helps determining the time of the onset of a destructive earthquake, its strength and the coordinates of the epicentre, predicting the time of the descent of glaciers and landslides long before the event. In medicine, the methodology predicts the severity of a disease and forecast of its aggravation.